Dr. Robert Brockelesby Davis - Sphurti Pusukuri (Telangana Journal of Psychiatry, 2020)
Dr. Robert B. Davis was one of the eminent figures shaping the field of Psychiatry in India. He was one of the founding member of the Indian Psychiatric Society and served as the president. He drafted the first proposal of the Mental Health Act of India along with other eminent psychiatrists in 1949. He served as the Superintendent and developed the European Mental Hospital (now known as the Central Institute of Psychiatry) in Ranchi into a leading centre for Psychiatry in India. He started the Kishore Nursing Home (now known as the Davis Institute of Neuropsychiatry) along with his wife. He was a passionate postgraduate teacher and a pioneer for introduction of several significant treatment procedures in India. He was awarded the Padma Shree in 1966 for his contributions to the field.